Persiapan Pembuatan Modul Penunjang Jabatan Fungsional Dosen - Cahyadi Husadha; Istianingsih Istianingsih; Wastam Wahyu Hidayat; Ery Teguh Prasetyo; Adelina Suryati; Robertus Suraji (Jurnal Pemberdayaan Umat, 2022)
Purpose: The purpose of community service that the Team does is an awareness, reasoning, and is a reflection of the long journey of lecturers in managing the functional positions of lecturers, of course with the aim of making outputs from various researches and lecturers' services from the point of view and knowledge of each lecturer. Method: This service method is carried out through webinars/teleconferences/discussion-meetings, and clinic-coaching. The team explored more deeply, and chose the goals of service, working methods, and the team's analytical power of written lecturer data and the results of the evaluation summary. Result: The results of the service obtained an understanding that; In managing the functional positions of lecturers, in addition to tips and tricks, real work is needed which is realized in the form of modules/books that have a high cumulative value in assessing the quality score of functional promotions for lecturers. Lecturers need coaching clinics as a manifestation of their work in the form of modules/books facilitated by institutions/universities in terms of publications, ISBN registration, and for the welfare of lecturers in the form of incentives for lecturers to be motivated. Conclusions: The conclusion of the service is declared positive and has a beneficial impact on all elements of higher education.